The business cycle today : fiftieth anniversary colloquium 1 - Zarnowitz, Victor; National Bureau of Economic Research (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1972)
To commemorate its 50th anniversary the National Bureau of Economic Research sponsored a series of colloquia to explore the effects of pending and anticipated policy issues on future research priorities for areas of long standing bureau concern. This volume of the fiftieth Anniversary Series contains the proceedings of the Business Cycle Today, a colloquium held in New York City.
Includes bibliographical references and index.
gp 21/01/2019
Loans
Keywords: Business cycles; Growth cycles; United States